2022
DOI: 10.1186/s12903-022-02532-4
|View full text |Cite
|
Sign up to set email alerts
|

The antibiofilm activity of selected substances used in oral health prophylaxis

Abstract: Oral health is a window to a patient’s general well-being. Balance in oral microbiome functions is crucial for health maintenance. A state of oral dysbiosis may lead to a variety of local and systemic pathological conditions. The presence of dental plaque is related to the majority of oral infections. Proper oral hygiene is crucial and the most economic practice contributing to oral health prophylaxis. Aside from prophylactic treatments provided by dental practitioners, mouth rinses, containing antimicrobial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…is another genus often isolated and present in the canine oral cavity and recognized for its role in developing dental plaque and periodontal disease [17]. Enterococcus faecalis (E. faecalis), specifically, forms biofilms in oral cavities, contributes to oral diseases and can efficiently be reduced by natural antimicrobials [18]. The bacteriostatic effect of natural antimicrobials against E. faecalis on dental plaque was directly confirmed with many flavonoids (luteolin, morin, naringin, quercetin and rutin) [19].…”
Section: Introductionmentioning
confidence: 99%
“…is another genus often isolated and present in the canine oral cavity and recognized for its role in developing dental plaque and periodontal disease [17]. Enterococcus faecalis (E. faecalis), specifically, forms biofilms in oral cavities, contributes to oral diseases and can efficiently be reduced by natural antimicrobials [18]. The bacteriostatic effect of natural antimicrobials against E. faecalis on dental plaque was directly confirmed with many flavonoids (luteolin, morin, naringin, quercetin and rutin) [19].…”
Section: Introductionmentioning
confidence: 99%
“…This result is slightly higher, ranging from a few to a dozen percent, than the reduction observed in our study. In another paper, the average reductions in C. albicans biofilm were reported to be as much as 60.9% [31] and 70.6% [32]. Such a significant difference may be attributed to variations in research methodology; for example, hydroxyapatite disks were used for biofilm extraction and the quantification of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, biofilm reduction with other mouthwashes ranged from 26.4% to 38.6%. Dudek-Wicher et al demonstrated the most potent eradication against C. albicans biofilm with PHMB at 83.6% and CPC at 84.2% [32]. The eradication of C. albicans biofilm from fibroblast-covered cellulose carriers by PHMB was reported to be between 70% and 80%.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is because they exist in biofilms on the surfaces of teeth, which are poorly penetrated by cationic agents such as cetylpyridinium (Wade 2000). Nonetheless, cetylpyridinium-containing mouthwashes have been shown to suppress salivary bacterial counts by 40-60% for up to 5 h (Jenkins et al 1994) and are highly effective at suppressing growth of and/or eradicating bacteria from biofilms ex vivo (Roberts et al 1981;Jenkins et al 1994;Otten et al 2011;Dudek-Wicher et al 2022). Cetylpyridinium-based mouthwash has also been found to markedly blunt increases in salivary and plasma NO2following an oral NO3load (Woessner et al 2016).…”
Section: Discussionmentioning
confidence: 99%